Nickel-cobalt-manganese ternary cathode material nanorods and their applications

The nickel, cobalt, manganese, aluminum, and lithium mixed metal salt solution with 8-hydroxyquinoline alcohol solution was calcined to obtain nickel, cobalt, manganese ternary cathode material nanorods, which solved the problem of ammonia nitrogen wastewater and resource waste in the prior art, achieved environmentally friendly and efficient preparation of cathode material, and improved the electrochemical performance of the material.

CN114551861BActive Publication Date: 2025-03-25GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210076940.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-24
Publication Date
2025-03-25
Estimated Expiration
2042-01-24

AI Technical Summary

Technical Problem

During the preparation of the positive electrode materials of existing lithium-ion batteries, a large amount of ammonia nitrogen wastewater is generated, and resources are wasteful and pollution is large. In traditional processes, the leaching solution adjusts to a higher pH to remove iron and aluminum, consumes alkali liquid and insufficient doping of aluminum.

Method used

A mixed metal salt solution of nickel, cobalt, manganese, aluminum and lithium is mixed with an alcohol solution of 8-hydroxyquinoline. After heating and reaction, alkali solution is added to adjust the pH. A nickel, cobalt, manganese ternary positive electrode material nanorod is prepared by calcination. This process directly utilizes waste ternary cathode material, short process, saves alkaline consumption, and allows aluminum to enter the cathode material as doped elements.

Benefits of technology

The preparation process of ammonia-free wastewater is realized, resource utilization is improved, environmental protection and personnel safety are guaranteed, and the electrochemical performance and aluminum doping effect of the cathode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114551861B_ABST
    Figure CN114551861B_ABST
Patent Text Reader

Abstract

The present invention discloses a nickel-cobalt-manganese ternary positive electrode material nanorod and its application. The chemical formula of the nickel-cobalt-manganese ternary positive electrode material nanorod is LiNi 1‑x‑y‑z Co x Mn y Al z O2, wherein 0<x<1, 0<y<1, 0≤z≤0.05, and the cross-sectional diameter of the nickel-cobalt-manganese ternary positive electrode material nanorod is 50-200nm, and the length is 0.1-5μm. The present invention generates a precipitate containing nickel-cobalt-manganese-aluminum-lithium by complexing and precipitating a mixed metal salt solution of nickel, cobalt, manganese, aluminum, and lithium with 8-hydroxyquinoline, and then calcining to obtain the ternary positive electrode material nanorod. The whole process does not generate ammonia nitrogen wastewater like the traditional process, and the alcohol used in the process can be directly recovered by evaporation and condensation, which is extremely environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a nickel-cobalt-manganese ternary positive electrode material nanorod and an application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic products, electric vehicles, energy storage systems and other fields due to their many advantages such as high energy density, low self-discharge, no memory effect, long cycle life, and low environmental pollution. Today, with the growing market demand for high-performance batteries such as high energy density and the increasing popularity of electric vehicles, the market demand for battery cathode materials has shown a rapid growth trend.

[0003] In the preparation of positive electrode materials, the transition metal needs to be prepared into a precursor liquid, and then a precipitation reaction is carried out with a precipitant and ammonia water to obtain the precursor. However, this process will produce a large amount of ammonia nitrogen wastewater. The positive electrode material can only be obtained after the prepared precursor is sintered with the lithium source. The overall process is long, with serious waste of resources and great pollution. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a nickel-cobalt-manganese ternary positive electrode material nanorod and its application.

[0005] According to one aspect of the present invention, a nickel-cobalt-manganese ternary positive electrode material nanorod is provided, wherein the chemical formula of the nickel-cobalt-manganese ternary positive electrode material nanorod is LiNi 1-x-y-z Co x Mn y Al z O2, wherein 0<x<1, 0<y<1, 0≤z≤0.05, the cross-sectional diameter of the nickel-cobalt-manganese ternary positive electrode material nanorod is 50-200nm, and the length is 0.1-5μm; the preparation method of the nickel-cobalt-manganese ternary positive electrode material nanorod comprises the following steps:

[0006] S1: mixing a mixed metal salt solution of nickel, cobalt, manganese, aluminum and lithium with an alcohol solution of 8-hydroxyquinoline, heating and reacting for a period of time, adding an alkali solution to adjust the pH, continuing the reaction for a period of time, and separating the solid and the liquid to obtain a solid material, wherein the alkali solution is at least one of sodium carbonate or potassium carbonate;

[0007] S2: The solid material is calcined under oxygen conditions to obtain the nickel-cobalt-manganese ternary positive electrode material nanorods.

[0008] In some embodiments of the present invention, in step S1, the mixed metal salt solution is prepared by the following method: acid leaching the waste ternary positive electrode material to obtain a leachate, removing iron from the leachate to obtain an iron-removed liquid, adjusting the molar ratio of each metal ion in the iron-removed liquid to obtain the mixed metal salt solution. Waste ternary positive electrode materials are used as raw materials for producing ternary positive electrode materials, directly from the battery recovery end to the positive electrode material end, and the process is shortened. In the traditional battery recycling process, the leachate needs to be adjusted to a higher pH to remove iron and aluminum. The present invention only needs to remove iron, saving the consumption of alkali solution, and at the same time, aluminum is introduced into the subsequent positive electrode material as a doping element to improve the performance of the positive electrode material.

[0009] In some embodiments of the present invention, the leaching solution is further subjected to a copper removal process by adding iron powder before iron removal.

[0010] In some preferred embodiments of the present invention, the iron removal is performed by adjusting the pH of the leaching solution to 3.2-3.5, and performing solid-liquid separation to obtain the iron-removed liquid.

[0011] In some preferred embodiments of the present invention, the molar ratio of each metal ion in the deironing solution is adjusted by adding at least one of soluble salts of nickel, cobalt, manganese, aluminum or lithium to the deironing solution so that the molar ratio of each metal ion meets the target product requirements, that is, Li:Ni:Co:Mn:Al=1:(1-xyz):x:y:z. Furthermore, the soluble salt is at least one of sulfate, chloride or acetate.

[0012] In some embodiments of the present invention, in step S1, the total concentration of metal ions in the mixed metal salt solution is 0.1-1.0 mol / L.

[0013] In some embodiments of the present invention, in step S1, the concentration of the 8-hydroxyquinoline alcohol solution is 0.3-0.6 mol / L.

[0014] In some preferred embodiments of the present invention, in step S1, the alcohol in the alcohol solution of 8-hydroxyquinoline is at least one of ethanol or ethylene glycol.

[0015] In some embodiments of the present invention, in step S1, the ratio of the total molar amount of metal ions in the mixed metal salt solution to the molar amount of 8-hydroxyquinoline in the alcohol solution of 8-hydroxyquinoline is 2:(3-5).

[0016] In some embodiments of the present invention, in step S1, the heating temperature is 50-70° C. Preferably, the heating reaction time is 1-2 hours.

[0017] In some embodiments of the present invention, in step S1, the pH is 9-11. Preferably, the reaction time after adding sodium carbonate to adjust the pH is 10-30 minutes.

[0018] In some embodiments of the present invention, in step S2, the calcination temperature is 700-950° C. Preferably, the calcination time is 4-8 hours.

[0019] In some embodiments of the present invention, in step S2, the washing is firstly washing with water and then washing with ethanol.

[0020] The present invention also provides the use of the nickel-cobalt-manganese ternary positive electrode material nanorods in lithium ion batteries.

[0021] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:

[0022] 1. The present invention uses a mixed metal salt solution of nickel, cobalt, manganese, aluminum, and lithium to complex and precipitate with 8-hydroxyquinoline to generate a precipitate containing nickel, cobalt, manganese, aluminum, and lithium, and then calcines it to obtain a ternary positive electrode material nanorod. The whole process does not produce ammonia nitrogen wastewater like the traditional process, and the alcohol used in the process can be directly recovered by evaporation and condensation, which is extremely environmentally friendly and harmless to the human body. The mixed metal salt solution of nickel, cobalt, manganese, aluminum, and lithium can be directly obtained by simply removing iron from the acid leaching solution of waste ternary lithium batteries.

[0023] 2. After calcination, there is basically no impurity residue in the 8-hydroxyquinoline co-precipitate, and with the disappearance of 8-hydroxyquinoline, the gaps in the crystal structure are larger, forming holes. When used as a positive electrode material, it is beneficial to the infiltration of the electrolyte and the transmission between ions, thereby greatly improving the electrochemical performance of the material.

[0024] 3. In the traditional battery recycling process, the leaching solution is adjusted to a higher pH to remove iron and aluminum. The present invention only needs to remove iron, saving the consumption of alkali solution, and at the same time, aluminum is introduced into the subsequent positive electrode material as a doping element to improve the performance of the positive electrode material.

[0025] 4. Compared with the traditional process of using P204, P507 and other extractants to extract nickel, cobalt and waste manganese, the valuable metals in the present invention are all recovered and utilized. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0027] Figure 1 This is a SEM image of the nickel-cobalt-manganese ternary positive electrode material nanorods prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0029] Example 1

[0030] This example prepares a nickel-cobalt-manganese ternary positive electrode material nanorod with a chemical formula of LiNi 0.33 Co 0.33 Mn 0.33 Al 0.01 O2, Figure 1 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary positive electrode material nanorods. The cross-sectional diameter of the nanorods is 80nm to 100nm, and the length is 0.1-5μm. The specific preparation process is:

[0031] Step 1, removing iron from the leaching solution obtained after acid leaching of the waste ternary lithium-ion battery to obtain a deironized solution, and adjusting the pH of the leaching solution to 3.2-3.5 when removing iron, without removing aluminum;

[0032] Step 2, adding a soluble salt of nickel, cobalt, manganese, aluminum or lithium to the iron-removed liquid so that the molar ratio of each metal ion meets the target product requirements, that is, Li:Ni:Co:Mn:Al=1:0.33:0.33:0.33:0.01, the soluble salt is a chloride salt, and a mixed metal salt solution is obtained, and the total concentration of metal ions in the mixed metal salt solution is 0.3 mol / L;

[0033] Step 3, preparing an ethanol solution of 8-hydroxyquinoline with a concentration of 0.6 mol / L;

[0034] Step 4, mixing the mixed metal salt solution in step 2 with the alcohol solution of 8-hydroxyquinoline in step 3 at a ratio of the total molar amount of metal ions to the molar amount of 8-hydroxyquinoline of 2:3 to obtain a mixed solution;

[0035] Step 5, heating the mixed solution in a water bath at 70°C for 1 hour;

[0036] Step 6, adding sodium carbonate to the mixed solution, adjusting the pH of the mixed solution to 11, and continuing the water bath reaction for 10 minutes;

[0037] Step 7, solid-liquid separation to obtain a solid material;

[0038] Step 8, washing the solid material with pure water first, and then with ethanol;

[0039] Step 9, drying after washing to obtain a dry material;

[0040] Step 10, calcining the dry material in an oxygen atmosphere at a temperature of 950° C. for 4 hours to obtain nickel-cobalt-manganese ternary positive electrode material nanorods.

[0041] Example 2

[0042] This example prepares a nickel-cobalt-manganese ternary positive electrode material nanorod with a chemical formula of LiNi 0.5 Co 0.2 Mn 0.25 Al 0.05 O2, the cross-sectional diameter of the nanorods is 50nm to 80nm, and the length is 0.1-5μm. The specific preparation process is:

[0043] Step 1, removing iron from the leaching solution obtained after acid leaching of the waste ternary lithium-ion battery to obtain a deironized solution, and adjusting the pH of the leaching solution to 3.2-3.5 when removing iron, without removing aluminum;

[0044] Step 2, adding soluble salts of nickel, cobalt, manganese, aluminum and lithium to the iron-removed liquid so that the molar ratio of each metal ion meets the target product requirements, that is, Li:Ni:Co:Mn:Al=1:0.5:0.2:0.25:0.05, the soluble salt is acetate, and a mixed metal salt solution is obtained, and the total concentration of metal ions in the mixed metal salt solution is 0.1 mol / L;

[0045] Step 3, preparing an ethylene glycol solution of 8-hydroxyquinoline with a concentration of 0.3 mol / L;

[0046] Step 4, mixing the mixed metal salt solution in step 2 with the alcohol solution of 8-hydroxyquinoline in step 3 at a ratio of the total molar amount of metal ions to the molar amount of 8-hydroxyquinoline of 2:4 to obtain a mixed solution;

[0047] Step 5, heating the mixed solution in a water bath at 60°C for 1.5 hours;

[0048] Step 6, adding sodium carbonate to the mixed solution, adjusting the pH of the mixed solution to 10, and continuing the water bath reaction for 20 minutes;

[0049] Step 7, solid-liquid separation to obtain a solid material;

[0050] Step 8, washing the solid material with pure water first, and then with ethanol;

[0051] Step 9, drying after washing to obtain a dry material;

[0052] Step 10, calcining the dry material in an air atmosphere at a temperature of 850° C. for 6 hours to obtain nickel-cobalt-manganese ternary positive electrode material nanorods.

[0053] Example 3

[0054] This example prepares a nickel-cobalt-manganese ternary positive electrode material nanorod with a chemical formula of LiNi 0.8 Co 0.1 Mn 0.08 Al 0.02 O2, the cross-sectional diameter of the nanorods is 150nm to 200nm, and the length is 0.1-5μm. The specific preparation process is:

[0055] Step 1, removing iron from the leaching solution obtained after acid leaching of the waste ternary lithium-ion battery to obtain a deironized solution, and adjusting the pH of the leaching solution to 3.2-3.5 when removing iron, without removing aluminum;

[0056] Step 2, adding soluble salts of nickel, cobalt, manganese, aluminum and lithium to the iron-removed liquid so that the molar ratio of each metal ion meets the requirements of the target product, that is, Li:Ni:Co:Mn:Al=1:0.8:0.1:0.08:0.02, the soluble salt is sulfate, and a mixed metal salt solution is obtained, and the total concentration of metal ions in the mixed metal salt solution is 1.0 mol / L;

[0057] Step 3, preparing an ethylene glycol solution of 8-hydroxyquinoline with a concentration of 0.6 mol / L;

[0058] Step 4, mixing the mixed metal salt solution in step 2 with the alcohol solution of 8-hydroxyquinoline in step 3 at a ratio of the total molar amount of metal ions to the molar amount of 8-hydroxyquinoline of 2:5 to obtain a mixed solution;

[0059] Step 5, heating the mixed solution in a water bath at 50°C for 2 hours;

[0060] Step 6, adding sodium carbonate to the mixed solution, adjusting the pH of the mixed solution to 9, and continuing the water bath reaction for 30 minutes;

[0061] Step 7, solid-liquid separation to obtain a solid material;

[0062] Step 8, washing the solid material with pure water first, and then with ethanol;

[0063] Step 9, drying after washing to obtain a dry material;

[0064] Step 10, calcining the dry material in air or oxygen atmosphere at 700° C. for 8 h to obtain ternary positive electrode material nanorods.

[0065] Test example

[0066] The nickel cobalt manganese oxide obtained in Examples 1-3 and commercially available NCM333, NCM523, and NCM811 were respectively used as lithium ion battery positive electrode materials to assemble button batteries for lithium ion battery electrochemical performance testing. The specific steps are: using N-methylpyrrolidone as a solvent, the positive electrode active material is mixed with acetylene black and PVDF in a mass ratio of 8:1:1, coated on aluminum foil, and dried at 80°C for 8h, and then vacuum dried at 120°C for 12h. The battery was assembled in an argon-protected glove box, the negative electrode was a metal lithium sheet, the diaphragm was a polypropylene film, and the electrolyte was 1M LiPF6-EC / DMC (1:1, v / v). The current density was 1C=160mA / g, and the charge and discharge cut-off voltage was 2.7-4.3V. The cycle performance at 1C current density was tested, and the results are shown in Table 1.

[0067] Table 1 Electrochemical properties of lithium nickel cobalt manganese oxide

[0068] 0.1C discharge capacity mAh / g Discharge capacity after 100 cycles mAh / g Cycle retention rate Example 1 168 164.8 98% Commercially available NCM333 166 162.6 98% Example 2 174 168.0 96.5% Commercially available NCM523 172 165.3 96.1% Example 3 204 184.3 90.3% Commercially available NCM811 205 184.5 90%

[0069] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing nickel-cobalt-manganese ternary positive electrode material nanorods, characterized in that: The following steps are involved: S1: mixing a mixed metal salt solution of nickel, cobalt, manganese, aluminum and lithium with an alcohol solution of 8-hydroxyquinoline, heating and reacting for a period of time, adding an alkali solution to adjust the pH, continuing the reaction for a period of time, and separating the solid and the liquid to obtain a solid material, wherein the alkali solution is at least one of sodium carbonate or potassium carbonate; S2: calcining the solid material under oxygen conditions to obtain the nickel-cobalt-manganese ternary positive electrode material nanorods; The general chemical formula of the nickel-cobalt-manganese ternary positive electrode material nanorods is LiNi 1-x-y-z Co x Mn y Al z O2, wherein 0<x<1, 0<y<1, 0<z≤0.05, and the cross-sectional diameter of the nickel-cobalt-manganese ternary positive electrode material nanorods is 50-200nm and the length is 0.1-5μm.

2. The preparation method according to claim 1, characterized in that: In step S1, the mixed metal salt solution is prepared by the following method: acid leaching the waste ternary positive electrode material to obtain a leachate, removing iron from the leachate to obtain a deironed liquid, and adjusting the molar ratio of each metal ion in the deironed liquid to obtain the mixed metal salt solution.

3. The preparation method according to claim 2, characterized in that: The method for adjusting the molar ratio of each metal ion in the deironing liquid is to add at least one soluble salt of nickel, cobalt, manganese, aluminum or lithium to the deironing liquid so that the molar ratio of each metal ion meets the target product requirements, that is, Li:Ni:Co:Mn:Al=1:(1-xyz):x:y:z.

4. The preparation method according to claim 1, characterized in that: In step S1, the total concentration of metal ions in the mixed metal salt solution is 0.1-1.0 mol / L.

5. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the 8-hydroxyquinoline alcohol solution is 0.3-0.6 mol / L.

6. The preparation method according to claim 1, characterized in that: In step S1, the ratio of the total molar amount of metal ions in the mixed metal salt solution to the molar amount of 8-hydroxyquinoline in the alcohol solution of 8-hydroxyquinoline is 2:(3-5).

7. The preparation method according to claim 1, characterized in that: In step S1, the heating temperature is 50-70°C.

8. The preparation method according to claim 1, characterized in that: In step S1, the pH is 9-11.

9. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 700-950°C.

10. Use of nickel-cobalt-manganese ternary positive electrode material nanorods prepared by the preparation method according to claim 1 in lithium-ion batteries.